TELEVISION FOR DEVELOPMENT IN AFRICA - Lellan, Iain Mc (Fréquence Sud, 2021)
ABSTRACT In N’Zikpli, a small village without electricity in central Ivory Coast, the elders of the community were asked about what they had learned from the battery-powered television the government had installed in the local school in 1974. After explaining, through an interpreter, that they had learned a lot about life outside the village, the men were asked if they had any questions about what they had seen. The chief was the first to speak: «Is it true that the white man can fly without wings?» «Why are whites always stabbing, punching and shooting each other?» another man asked.